2019
DOI: 10.3389/fmicb.2019.00088
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Bacterial Community Structure Drives Different Atrazine-Degrading Efficiencies

Abstract: Compositions of pollutant-catabolic consortia and interactions between community members greatly affect the efficiency of pollutant catabolism. However, the relationships between community structure and efficiency of catabolic function in pollutant-catabolic consortia remain largely unknown. In this study, an original enrichment (AT) capable of degrading atrazine was obtained. And two enrichments – with a better/worse atrazine-degrading efficiency (ATB/ATW) – were derived from the original enrichment AT by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Previous studies already showed the adverse effects of ATZ on the structure of soil microbial communities after longterm exposure. [36][37][38][39][40] Here, we documented the chronic adverse effects of NPATZs on the rhizosphere bacterial communities of L. sativa. For instance, it was found that 6 months of soil treatment with ATZ decreased the diversity and evenness of the bacterial community of the soil compared to the control.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies already showed the adverse effects of ATZ on the structure of soil microbial communities after longterm exposure. [36][37][38][39][40] Here, we documented the chronic adverse effects of NPATZs on the rhizosphere bacterial communities of L. sativa. For instance, it was found that 6 months of soil treatment with ATZ decreased the diversity and evenness of the bacterial community of the soil compared to the control.…”
Section: Discussionmentioning
confidence: 97%
“…In the latter case, the specialists may well have been outcompeted by those growing on the amendments as a result of competition for oxygen, for vitamins or for essential nutrients. Indeed, many reports indicate that indigenous microbial populations are good candidates for the breakdown of aromatic compounds that pollute the environment that they live in (Ren et al, 2015;Liu et al, 2019). More detailed studies also showed a clear correlation between expression of tfdA and cad genes involved in phenoxyacetic acid degradation and mineralisation rate of these herbicides along with the evolution of the soil microbial communities (Baelum et al, 2008;Ditterich et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Soil and water pollution by atrazine is a persistent problem worldwide, and poses a considerable threat to the health of soil ecosystem, and adversely influences the soil biological processes by altering soil enzymatic activities, soil microbial population and community diversity [ 45 – 47 ]. Therefore, it is crucial to find a practical solution for the remediation of atrazine -contaminated environments.…”
Section: Discussionmentioning
confidence: 99%